Seroprevalence of Mycobacterium avium Complex in Wild Mammals in the Iberian Peninsula - MATOS, A. C.; FIGUEIRA, L.; MATOS, M.; PINTO, M. L.; COELHO, A. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
A retrospective serologic survey was conducted for antibodies against MAC in a random sample of 623 free-ranging wild mammals killed on roads and by hunters, or found dead in east-central Portugal. Animals were tested for antibodies to Mycobacterium avium complex with a commercial enzyme linked assay. The seroprevalence of Mycobacterium avium complex infection was 4.7% (n=29; CI 95%: 25.4 - 32.7%). Antibodies against MAC were detected in 4 out of 11 animal species included in this study, consisted of 1/42 red fox (Vulpes vulpes) (2.4%; CI 95%: 0.0-4.0%), 1/6 Eurasian otter (Lutra lutra) (16.7%), 1/3 European badger (Meles meles) (33.3%), and 26/109 wild boar (Sus scrofa) (23.9%; CI 95%: 17.8-34.2%). Infection was found in three taxonomic families: 2.4% (CI 95%: 0.0-4.0%) in Canidae, 16.7% (CI 95%: 0.0-37.8%) in Mustelidae, and 23.9% (CI 95%: 17.8-34.2%) in Suidae. No positive sera were found in the common genet, Egyptian mongoose, beech marten, hedgehog, wild rabbit, red deer or fallow deer. Results of the present study indicate that antibodies against MAC were present in wild carnivores and wild boars in Iberian Peninsula. According to the test sensitivity and specificity claimed by the manufacturer, the true prevalence Mycobacterium avium complex infection among wild mammals in the Iberian Peninsula was calculated to be between 10.7% and 13.6%.